All‐donor poly(arylene‐ethynylene)s containing anthracene and silole‐based units: Synthesis, electronic, and photovoltaic properties. Issue 22 (18th September 2013) - Grisorio, Roberto; Suranna, Gian Paolo; Mastrorilli, Piero; Allegretta, Giovanni; Loiudice, Anna; Rizzo, Aurora; Gigli, Giuseppe; Manoli, Kyriaki; Magliulo, Maria; Torsi, Luisa
ABSTRACT The manuscript deals with the synthesis and properties of four new all‐donor alternating poly(arylene‐ethynylene)s DBSA, DBSTA, DTSA, and DTSTA. The polymers have been obtained by a Sonogashira cross‐coupling of 9, 10‐diethynyl‐anthracene with the dibromo‐derivatives of 9, 9‐dioctyl‐dibenzosilole (DBSA), 2, 7‐dithienyl‐9, 9‐dioctyl‐dibenzosilole (DBSTA), 4, 4‐dioctyl‐dithienosilole (DTSA), or 2, 6‐dithienyl‐9, 9‐dioctyl‐dithienosilole (DTSTA). The polymers exhibited absorption profiles and frontier orbital energies strongly dependent on their primary structure. Density functional theory calculations confirmed experimental observations and provided an insight into the electronic structure of the macromolecules. In particular, the effects exerted by the thiophene units in DBSTA and DTSTA on the optical properties of the corresponding polymers could be rationalized with respect to DBSA and DTSA. Preliminary photovoltaic measurements have established that the performance of DTSA is among the highest reported for an all‐donor polymer. Moreover, UV irradiation of DTSA films under air evidenced a remarkable photostability of this material, providing further evidence that ethynylene‐containing electron‐rich systems are promising donors for organic solar cells applications. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4860–4872